A survey of disease connections for CD4+ T cell master genes and their directly linked genes. (December 2015) - Li, Wentian; Espinal-Enríquez, Jesús; Simpfendorfer, Kim R.; Hernández-Lemus, Enrique
Abstract : Highlights: CD4+ T cell subtype master genes and their connected genes are more likely to be associated with a disease or a phenotype. Genes connected to the CD4+ T cell subtype master genes are more likely to be transcription factors. CD4+ T cell subtype master genes and their connected genes are more likely to be haploinsufficient. CD4+ T cell subtype master genes and their connected genes are more likely to be embryonic lethal gene (essential genes). Abstract: Genome-wide association studies and other genetic analyses have identified a large number of genes and variants implicating a variety of disease etiological mechanisms. It is imperative for the study of human diseases to put these genetic findings into a coherent functional context. Here we use system biology tools to examine disease connections of five master genes for CD4+ T cell subtypes ( TBX21, GATA3, RORC, BCL6, and FOXP3 ). We compiled a list of genes functionally interacting (protein–protein interaction, or by acting in the same pathway) with the master genes, then we surveyed the disease connections, either by experimental evidence or by genetic association. Embryonic lethal genes (also known as essential genes) are over-represented in master genes and their interacting genes (55% versus 40% in other genes). Transcription factors are significantly enriched among genes interacting with the master genes (63% versus 10% in other genes). Predicted haploinsufficiency is a feature of most these genes. Disease-connected genes are enriched in this list of genes: 42% of these genes have a disease connection according to Online Mendelian Inheritance in Man (OMIM) (versus 23% in other genes), and 74% are associated with some diseases or phenotype in a Genome Wide Association Study (GWAS) (versus 43% in other genes). Seemingly, not all of the diseases connected to genes surveyed were immune related, which may indicate pleiotropic functions of the master regulator genes and associated genes.